A patient safety escape room simulation for internal medicine learners, based on hazards identified in local incident reports (Canadian Medical Education Journal, 2026)
Implication StatementPhysicians at our centre have enthusiastically supported a Quality Improvement initiative aimed at achieving a high proportion of physician-submitted incident reports. We uncovered some serious safety incidents and recurring safety themes based on review of these physician-submitted reports and decided to embed these local data in a realistic simulation scenario. Our innovative escape room format for the simulation was an engaging and effective way to teach medical learners about patient safety concepts and how to recognize and respond to safety incidents. We encourage colleagues at other centres to try this strategy for delivering patient safety education!